Influence of Different Climatic Regions on the Energy Efficiency Standard Index of Variable Refrigerant Flow System - Chen Huanxin; Zeng Yuke; Cheng Jianhong; Shao Shuangquan; Zhang Jianqiang; Chen Jin; Zhang Menghua (Zhileng xuebao)
With the development and popularization of variable refrigerant flow (VRF) systems, the research on the energy efficiency standard of VRF systems has gradually increased. Three major energy efficiency standard indices (SEER, HSPF, and IPLV(C)) are closely related to the cooling/heating hours for ambient temperature. From the perspective of geographical environment, the influence of different climate regions on the energy efficiency standards in combination with the development of international energy efficiency standards of the VRF system was analyzed in this study. Energy efficiency standard evaluation by zoning is a novel perspective.It is expected that the scholars and enterprises in the field of heating, ventilation, and air conditioning will actively participate in exploring the advantages and disadvantages of standard zoning or nonzoning from the perspectives of theory and experiment to jointly promote industrial progress.